Six weeks of multistation program on the knee proprioception and performance of futsal players - Pérez-Silvestre, Á.; Albert-Lucena, D.; Gómez-Chiguano, G. F.; Plaza-Manzano, G.; Pecos-Martin, D.; Gallego-Izquierdo, T.; Martin-Casas, P.; Romero-Franco, N. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Proprioception and vertical jump are important parameters in the performance and prevention of injuries in futsal. However, very few studies have analyzed the role of multistation exercises to improve these variables. The purpose of this study was to assess the effects of a six-week multistation exercise program on knee joint position sense (JPS) and countermovement jump (CMJ) of futsal players. METHODS: Thirty-four male futsal players randomly classified into experimental (N.=17) or control group (N.=17). The experimental group included a multistation exercise protocol to their training routines (2 times/week - 6 weeks); the control group continued their training routines. All the players completed similar training routines outside of the multistation exercises. Before (baseline), just after the intervention (Post6Wk) and four weeks later (Post10Wk), CMJ and knee JPS (absolute, relative and variable angular error: AAE, RAE and VAE, respectively) were evaluated. RESULTS: ANOVA showed that the experimental group significantly decreased VAE at Post10Wk compared to baseline, suggestive of greater proprioceptive precision, while the control group significantly increased AAE, RAE and VAE at Post10Wk compared to baseline. The experimental group exhibited lower and thus, better AAE and VAE than the control group at Post10Wk, although no significant differences were found at Post6Wk. No significant differences was found in the CMJ. CONCLUSIONS: A six weeks of multistation program may help improve proprioceptive precision of futsal players, even one month after finishing the 6-wk multistation training program. However, this is not long enough to improve proprioceptive acuity and maximum vertical jump. Therefore, the meaningful of these results in term of performance are unclear.